Table of Content (Journal of natural sciences, life and applied sciences, 2025)
Table of Content:• Pollution In The Lagoons of Central-West Jeddah CityMs. Sara Husain Alghamdi, Asst-Prof. Abrar Abdulhadi Almalki• Evaluation of the Immunological Markers IL-10 and IL-12 in Patients with Systemic Lupus ErythematousLecturer / Ali Mohammed Abd-Alameer• Transcending Rational Principles: Mathematical Infinity as a Foundation for New Principles – Four Absolute Binary Theorems as a Basis for Absolute Infinite SystemsDr. Abdelrahman Yousif Bashclare
Keywords: Journal of Natural Sciences, Life and Applied Sciences